2006
DOI: 10.1111/j.1365-2869.2006.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dreaming induced by CPAP in severe obstructive sleep apnea syndrome patients

Abstract: SUMMARY To study dream content in patients with severe obstructive sleep apnea syndrome (OSAS) and its modification with Continuous Positive Airway Pressure (CPAP) therapy. We assessed twenty consecutive patients with severe OSAS and 17 healthy controls. Polysomnograms were recorded at baseline in patients and controls and during the CPAP titration night, 3 months after effective treatment and 2 years later in patients. Subjects were awakened 5-10 min after the beginning of the first and last rapid eye movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…In keeping with the finding in apnea patients (Carrasco et al 2006), an increased SWS amount and a lower number of awakenings during the recovery night drastically affect DR frequency (De Gennaro et al 2010), suggesting that a "lighter" sleep facilitates the retrieving process of dreams. Similarly, a study carried out with a 40-h multiple nap protocol revealed that lower frontal delta and reduction of centro-parietal sigma activity during the last 15 min of NREM sleep is related to DR (Chellappa et al 2011).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In keeping with the finding in apnea patients (Carrasco et al 2006), an increased SWS amount and a lower number of awakenings during the recovery night drastically affect DR frequency (De Gennaro et al 2010), suggesting that a "lighter" sleep facilitates the retrieving process of dreams. Similarly, a study carried out with a 40-h multiple nap protocol revealed that lower frontal delta and reduction of centro-parietal sigma activity during the last 15 min of NREM sleep is related to DR (Chellappa et al 2011).…”
Section: Discussionmentioning
confidence: 70%
“…In particular, insomnia patients recalled more dreams than healthy subjects (Schredl et al 1998) and the number of their nocturnal awakenings correlated with the number of dreams recalled (Charney et al 1977). Furthermore, a longitudinal investigation on patients with sleep apnea revealed a lower DR frequency in the first CPAP night, compared to the subsequent nights (Carrasco et al 2006). Therefore, a SWS rebound and a less fragmented sleep are related to a lower DR rate.…”
Section: Discussionmentioning
confidence: 96%
“…On the one hand, no differences in dream recall following REM awakenings compared with healthy controls were reported by Groß [5] or Carrasco et al [2]. Similarly, Schredl et al [23] found a high recall rate (75%) for induced awakenings of patients with sleep apnea.…”
Section: Traumerinnerungshäufigkeit Und Alptraumhäufigkeit Bei Patienmentioning
confidence: 90%
“…[21]). Second, sample sizes are often quite small in laboratory studies (N=33 [6], N=44 [23], N=20 [2]), so generalizations of nonsignificant findings are problematic due to insufficient statistical power. Within a larger sample of sleep apnea patients (N=238), Schredl [15] found that dream recall after a normal laboratory night without awakenings was lower compared with dream recall of healthy controls, with a small but significant correlation with the oxygen saturation nadir.…”
Section: Traumerinnerungshäufigkeit Und Alptraumhäufigkeit Bei Patienmentioning
confidence: 98%
“…Severe OSA can be associated with unpleasant dreams and nightmares, similar to RBD, which are controlled with nCPAP therapy [25]. In a controlled study involving 20 patients (19 males; mean age 51 years, range 34-66 years; mean AHI, 73.3 ± 25.3), although the frequency of dream recall was similar between OSA patients and controls, the OSA patients had significantly more emotional dreams and longer dreams, with aggressive and violent content.…”
Section: F) Nightmare Disordermentioning
confidence: 98%